The effect of surgery on functional outcomes of the elbow in adults with isolated capitellar fractures - Akalin, Yavuz; Ozturk, Alparslan; Ozkan, Yuksel; Cevik, Nazan; Aksakal, Ahmet Murat; Otuzbir, Ali (The European Research Journal, 2016)
Objectives. The aim of this study was to evaluate the factors affecting the functional outcomes together with the clinical and radiological findings obtained from the treatment of adult capitellar fractures through open reduction and internal fixation. Methods. Patients who applied our clinic between 2008 and 2013 with a mean age of 37.5 (range: 17-77) were treated surgically. A total of 11 patients, seven male, and four female, were included in the study. In the study, fracture types of the patients were determined according to McKee modification of the Bryan and Morrey classification. After the operation, patients were followed for an average 26 (15-63) months. In the radiological and clinical evaluations, carrying angle of the operated elbow was compared with the carrying angle values of the healthy elbow. Clinical assessment was made of the Mayo Elbow Performance Index (MEPI). Results. Patients were clinically assessed according to the MEPI scoring over 100 points. It was seen that five patients got 100 points (excellent) while 6 got 85 points (good). No significant difference was observed between fracture types regarding elbow flexion. Type III fractures were found to be significantly more limited than type I and type IV fractures regarding elbow extension degrees (p=0.040). Conclusions. This study yielded inferences that we considered important. Degenerative changes observed in type III fractures only show that this fracture type poses the risk of osteoarthritis development The fact that heterotopic ossification ossification causes movement restriction affect clinical findings adversely. We believe that degenerative arthritis would decrease, joint range could be maintained better, and functional results will be better by avoiding challenging passive exercise and suggesting active practice instead.